Justice, legality, and the rule of law lessons from the Pitcairn prosecutions - Oliver, Dawn. (Oxford : Oxford University Press, 2009)
In 2004 six Pitcairn men were convicted of numerous offences against girls and young women, but what right did the British government have to initiate these prosecutions? Was it fair given that no laws had been published on the island? Indeed what law was there on this island? This book explores the issues raised by the Pitcairn case.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Rule of law; Rule of law -- Great Britain; Rule of law -- Pitcairn Island -- Case studies; Trials (Sex crimes) -- Pitcairn Island -- Case studies